Probable evidence for a transient mega-electron volt emission line in the GRB 221023A - Lu-Yao Jiang; Yun Wang; Yu-Jia Wei; Da-Ming Wei; Xiang Li; Hao-Ning He; Jia Ren; Zhao-Qiang Shen; Zhi-Ping Jin (Nature Communications)
Abstract Detection of spectral line in gamma-ray bursts (GRBs) is importance for studying GRB physics, as it provides insights into the composition and physical conditions of the GRB environment. However, progress in detecting X-ray or gamma-ray emission and absorption lines in GRB spectra has been relatively slow, only the narrow emission line feature of about 10 MeV found in GRB 221009A has exhibited a significance exceeding 5σ. Here, we report the probable evidence of a narrow emission feature at about 2.1 mega-electron volts (MeV) in the spectrum of GRB 221023A. The highest statistical significance of this feature is observed in the time interval between 8 and 30 seconds after Fermi Gamma-Ray Burst Monito trigger, with the chance probability value  <2.56 × 10−5 (after accounting for the look-elsewhere effect), corresponding to a Gaussian-equivalent significance  >4.20σ. We interpret this festure as being generated through the de-excitation of excited electrons in the relativistic hydrogen-like high-atomic-number ions entrained in the GRB jet.